AKULTURASI KOMPETENSI BIDANG CHASIS KENDARAAN PADA KURIKULUM BERBASIS KERJASAMA INDUSTRI - Suhartanta, Suhartanta; Efendi, Yosep; Wakid, Muhkamad; Us, Tawardjono (Universitas Negeri Yogyakarta, 2023)
AbstractThe potential for human resource development in Chassis' area of expertise is still very broad. In addition, the time span of its usefulness is still very long because it is not displaced by the transition of electric vehicles. Therefore, it is important to conduct research that develops the competence of the Chassis area of expertise, which then cultures it into the curriculum and learning of automotive workshops and partner industries. This type of research is qualitative descriptive research. Data were collected through surveys, interviews, FGDs and observations in the automotive industry regarding wheel alignment competencies. The results showed that attitudes that can be observed and experienced developments when carrying out jobs in campus workshops and the chassis industry include accuracy in measuring chassis components, dexterity in carrying out the sequence of work and responsibility in working on vehicle maintenance and repair needs. In the aspect of automotive technology knowledge, components that can be observed for development includebasic knowledge, working principles, procedures, understanding of construction, knowledge of vehicle safety and security equipment requirements. Meanwhile, the ability to diagnose tire/wheel problems/damage skills according to manual repair procedures and skills in carrying out vehicle chassis maintenance procedures..